Screening of Chrysanthemum Cultivars for their Tolerance against Sucking Pests in Terai Region of West Bengal, India - Sidhya, Prabhas; Sarkar, Dipayan; Sarkar, Indrajit; Pal, Suprakash (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Chrysanthemum (Chrysanthemum morifolium Ramat.) is an important commercial flowering crop. This plant is often invaded by sucking pests like aphids, mealybugs and mites causing severe damage to the quality and quantity of flower yield. Searching for tolerant cultivars against these pests constitutes one of the most cost-effective pest management strategies. An experiment was conducted at Uttar Banga Krishi Viswavidyalaya, Pundibari, India to find out the reaction of forty different genotypes of spray chrysanthemum to aphids, mealybugs and mites. The results indicated that the genotypes exhibited significant variations in harbouring number of all the three sucking pests and the per cent plant infestation by aphids and mealybugs also varied significantly. The variation in pest infestation may be attributable to the genetic traits of these chrysanthemum cultivars. Out of all the genotypes tested the varieties Yellow Baby, Arka Kirti and Arka Yellow Gold were found to be the most tolerant against all the sucking pests and therefore, may be recommended for cultivation in the Terai agroclimatic region of West Bengal.